Multiaspect Sustainability Analysis of Household-Scale Coconut Sugar Enterprises in Besan Village, Klungkung - Kusumadewi, Putu Oktavia; Susrusa, Ketut Budi; Dewi, Ni Luh Prima Kemala (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 19 No 1 (2025), 2025)
Coconut sugar production plays a vital role in the rural economy, especially in Besan Village, Dawan Sub-district, Klungkung Regency. However, the sustainability of this enterprise is challenged by issues across economic, social, ecological, institutional, and technological dimensions. This study aims to analyze the sustainability status, identify sensitive attributes, and propose improvement scenarios for the coconut sugar enterprise in Besan Village. The research uses both quantitative and qualitative data obtained from primary and secondary sources, with data collected through questionnaires administered to key informants. The analysis employs the Multiaspect Sustainability Analysis (MSA) method. Findings reveal that the sustainability status is classified as low sustainable with a score of 44.56. Key sensitive attributes include environmental impact, financial record-keeping, social security ownership, access to financial institutions, and digital marketing adoption. The implementation of the first scenario raises the sustainability score to 70.51 ( sustainable ), while the second scenario increases it further to 88.47 ( very sustainable ). It is recommended that the prioritized improvement scenarios be implemented to enhance the long-term sustainability of the coconut sugar enterprise.